Modal analysis of functionally graded Timoshenko beam - Huyen, Nguyen Ngoc; Khiem, Nguyen Tien (Vietnam Journal of Mechanics, 2017)
Dynamic analysis of FGM Timoshenko beam is formulated in the frequency domain taking into account the actual position of neutral plane. The problem formulation enables to obtain explicit expressions for frequency equation, natural modes and frequency response of the beam subjected to external load. The representations are straightforward not only to modal analysis and modal testing of FGM Timoshenko beam with general end conditions but also to study coupling of axial and flexural vibration modes. Numerical study is carried out to investigate effect of true neutral axis position and material properties on the modal parameters.